Pengaruh Brand Image dan Personal Selling terhadap Purchase Intention (Studi Kasus di Institut Manajemen Wiyata Indonesia) - Bambang Somantri; Ane Nurranti Awalia (Cakrawala Repositori IMWI, 2021)
The purpose of this study to determine the effect of the dimensions or variables, brand image and personal selling to purchase intention. Design / methodology / approach: The research method used survey method using questionnaires distributed to 118 sample. While quality testing instruments Techniques include test validity and reliability testing. And techniques of data analysis using descriptive analysis and correlation, while to test the hypothesis, partial analysis (T test) and simultaneous (F test) are used. Results: Where as the two independent variables have a significant positive impact on purchase intention which is the brand image and personal selling. Study limitations / implications: The analysis was only performed on one branch and only two dimensions or variables are tested. Expected application of the marketing mix can be formulated and adapted to local environmental conditions and culture in order to be implemented.